2014
DOI: 10.1021/jp412160e
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Swelling Clay Particles at Finite Temperature upon Hydration

Abstract: The knowledge of mechanical properties of swelling clays on the scale of the clay layer is of crucial importance to build predictive hydromechanical macroscopic constitutive laws in a bottom-up approach. In this work, we computed the elastic properties of particles of a swelling clay (i.e., montmorillonite) by molecular dynamics simulations. Because of the softness of the material in the direction orthogonal to the clay layer with increasing water content, the computation of the whole stiffness tensor was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 52 publications
6
75
1
Order By: Relevance
“…However, experimental data obtained by acoustic or elastic wave measurements are known to provide higher values of elastic parameters than static measurements i.e., those associated with slower loading rates (e.g., Santamarina et al, 2001), as is the case for this study. Finally, the estimated undrained uniaxial Young's modulus provided by this study, i.e., 32.3 ± 3.9 GPa as well as the experimental data obtained by Zhang et al (2009) on a natural rectorite crystal and the theoretical results obtained by Carrier et al (2014) are found to be almost consistent. The Young's modulus of approximately 18 GPa obtained by Zhang et al (2009) for a single crystal of rectorite, which corresponds to the regular alternation of illite and montmorillonite layers, appears to logically lie in-between the values obtained by Carrier et al (2014) for dehydrated and monohydrated montmorillonite, respectively.…”
Section: Undrained Vs Drained Moduli As Seen From Strain Analysissupporting
confidence: 80%
See 4 more Smart Citations
“…However, experimental data obtained by acoustic or elastic wave measurements are known to provide higher values of elastic parameters than static measurements i.e., those associated with slower loading rates (e.g., Santamarina et al, 2001), as is the case for this study. Finally, the estimated undrained uniaxial Young's modulus provided by this study, i.e., 32.3 ± 3.9 GPa as well as the experimental data obtained by Zhang et al (2009) on a natural rectorite crystal and the theoretical results obtained by Carrier et al (2014) are found to be almost consistent. The Young's modulus of approximately 18 GPa obtained by Zhang et al (2009) for a single crystal of rectorite, which corresponds to the regular alternation of illite and montmorillonite layers, appears to logically lie in-between the values obtained by Carrier et al (2014) for dehydrated and monohydrated montmorillonite, respectively.…”
Section: Undrained Vs Drained Moduli As Seen From Strain Analysissupporting
confidence: 80%
“…Finally, the estimated undrained uniaxial Young's modulus provided by this study, i.e., 32.3 ± 3.9 GPa as well as the experimental data obtained by Zhang et al (2009) on a natural rectorite crystal and the theoretical results obtained by Carrier et al (2014) are found to be almost consistent. The Young's modulus of approximately 18 GPa obtained by Zhang et al (2009) for a single crystal of rectorite, which corresponds to the regular alternation of illite and montmorillonite layers, appears to logically lie in-between the values obtained by Carrier et al (2014) for dehydrated and monohydrated montmorillonite, respectively. This study's value of 32.3 ± 3.9 GPa lies between the theoretical data obtained by Carrier et al (2014) for the Na-montmorillonite with 1 or 0 interlayer water sheet.…”
Section: Undrained Vs Drained Moduli As Seen From Strain Analysissupporting
confidence: 80%
See 3 more Smart Citations